β-LacFamPred: An online tool for prediction and classification of β-lactamase class, subclass, and family - Pandey, Deeksha; Singhal, Neelja; Kumar, Manish (Frontiers in Microbiology, 2023)
β-lactams are a broad class of antimicrobial agents with a high safety profile, making them the most widely used class in clinical, agricultural, and veterinary setups. The widespread use of β-lactams has induced the extensive spread of β-Lactamase hydrolyzing enzymes known as β-Lactamases (BLs). To neutralize the effect of β-Lactamases, newer generations of β-lactams have been developed, which ultimately led to the evolution of a highly diverse family of BLs. Based on sequence homology, BLs are categorized into four classes: A to D in Ambler’s classification system. Further, each class is subdivided into families. Class B is first divided into subclasses B1, B2, and B3, and then each subclass is divided into families. The class to which a BL belongs gives a lot of insight into its hydrolytic profile. Traditional methods of determining the hydrolytic profile of BLs and their classification are time-consuming and require resources. Hence we developed a machine-learning-based in-silico method, named as β-LacFamPred, for the prediction and annotation of Ambler’s class, subclass, and 96 families of BLs. During leave-one-out cross-validation, except one, all β-LacFamPred model HMMs showed 100% accuracy. Benchmarking with other BL family prediction methods showed β-LacFamPred to be the most accurate. Out of 60 penicillin-binding proteins (PBPs) and 57 glyoxalase II proteins, β-LacFamPred correctly predicted 56 PBPs and none of the glyoxalase II sequences as non-BLs. Proteome-wide annotation of BLs by β-LacFamPred showed a very less number of false-positive predictions in comparison to the recently developed BL class prediction tool DeepBL. β-LacFamPred is available both as a web-server and standalone tool at http://proteininformatics.org/mkumar/blacfampred and GitHub repository https://github.com/mkubiophysics/B-LacFamPred respectively.